Body mass index and healthcare costs: a systematic literature review of individual participant data studies. (22nd May 2017) - Kent, Seamus; Fusco, Francesco; Gray, Alastair; Jebb, Susan A.; Cairns, Benjamin J.; Mihaylova, Borislava
Summary: Excess weight is associated with increased total healthcare costs, but it is less well known how the associations between excess weight and costs vary across different types of healthcare service. We reviewed studies using individual participant data to estimate associations between body mass index and healthcare costs, and summarized how annual healthcare costs for overweight (body mass index 25 to <30 kg/m 2 ) and obese (≥30 kg/m 2 ) individuals compared with those for healthy weight individuals (18.5 to <25 kg/m 2 ). EMBASE and MEDLINE were searched from January 1990 to September 2016, and 75 studies were included in the review. Of these, 34 studies presented adequate information to contribute to a quantitative summary of results. Compared with individuals at healthy weight, the median increases in mean total annual healthcare costs were 12% for overweight and 36% for obese individuals. The percentage increases in costs were highest for medications (18% for overweight and 68% for obese), followed by inpatient care (12% and 34%) and ambulatory care (4% and 26%). Percentage increases in costs associated with obesity were higher for women than men. The substantial costs associated with excess weight in different healthcare settings emphasize the need for investment to tackle this major public health problem.